2023
DOI: 10.3390/ijms241512133
|View full text |Cite
|
Sign up to set email alerts
|

Novel Matrix Metalloproteinase-9 (MMP-9) Inhibitors in Cancer Treatment

Zainab Ahmed Rashid,
Sanaa K. Bardaweel

Abstract: Matrix metalloproteinases (MMPs) belong to a family of zinc-dependent proteolytic metalloenzymes. MMP-9, a member of the gelatinase B family, is characterized as one of the most intricate MMPs. The crucial involvement of MMP-9 in extracellular matrix (ECM) remodeling underscores its significant correlation with each stage of cancer pathogenesis and progression. The design and synthesis of MMP-9 inhibitors is a potentially attractive research area. Unfortunately, to date, there is no effective MMP-9 inhibitor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 157 publications
0
9
0
Order By: Relevance
“…Unfortunately, as of now, none of the MMP-9 inhibitors have received FDA approval. 42 The selective antitumor efficacy of Mit-A observed in our study may be attributed to the cellular heterogeneity inherent in brain tumors. This heterogeneity is potentially rooted in the presence of GSCs, which are capable of initiating distinct tumor cell lineages post tumor initiation.…”
Section: ■ Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Unfortunately, as of now, none of the MMP-9 inhibitors have received FDA approval. 42 The selective antitumor efficacy of Mit-A observed in our study may be attributed to the cellular heterogeneity inherent in brain tumors. This heterogeneity is potentially rooted in the presence of GSCs, which are capable of initiating distinct tumor cell lineages post tumor initiation.…”
Section: ■ Discussionmentioning
confidence: 64%
“…To assess the potential therapeutic efficacy of inhibiting MMP-9 function in Mit-A responders, it is imperative to develop specific MMP-9 inhibitors that selectively target the tumor-promoting function while preserving its antitumor effects. Unfortunately, as of now, none of the MMP-9 inhibitors have received FDA approval …”
Section: Discussionmentioning
confidence: 99%
“…50 4.1.3. General Procedure for the Synthesis of the N-[2-((5-Mercapto-1,3,4-oxadiazol-2-yl)methoxy)phenyl]acetamide (3). For 6 h, a mixture of N-(2-(2-hydrazinyl-2-oxoethoxy)phenyl)acetamide (2) (0.017 mol, 3.87 g), carbon disulfide (0.025 mol, 1.90 g), and potassium hydroxide (0.025 mol, 1.40 g) in ethanol (50 mL) was refluxed.…”
Section: General Procedures For the Synthesis Of The Ethyl 2-(2-aceta...mentioning
confidence: 99%
“…Several studies have indicated that MMPIs (matrix metalloproteinase inhibitors) have the potential to impede cell proliferation by promoting apoptosis. 3 Heterocyclic compounds constitute 70% of the anticancer medications approved by the FDA between 2010 and 2020. 4 Heterocyclic rings exhibit their biological activity in different pathways owing to their ability to engage in various intermolecular interactions such as hydrogen bond donor/ acceptor characteristics, metal coordination complexes, Πstacking interactions, and van der Waals and hydrophobic forces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation